Le développement durable face à sa crise : un concept menacé, sous-exploité ou dépassé ? - Jacques Theys (Développement Durable et Territoires)
The concept of sustainable development seems progressively disappearing from the public and political debates, and partly from the scientific forefront – replaced by more “up to date” terms such as “resilience”, “transition”, “degrowth”, ”green economy”, “smart growth”…. That is, at least, the situation in France, which is not yet so much involved in the recent development of the “sustainability sciences” ongoing in the anglo-saxon countries. One possible explanation for this fading is that “sustainable development” has been deeply embedded in the context of the globalisation process which began at the end of the eighties and ended with the economic crisis in 2008. Another possible reason is the overuse – and misuse- which has been done of this badly defined notion during the last twenty years- with a weak efficiency: the ambiguity – which has strongly contributed to its historical success-, turns now to be a factor of distrust. This article – while sharing the two previous arguments- adds to them a third one: the crisis which the concept of sustainable development is facing is also related to the fact that its potential richness or specificity has not been fully “exploited” in the past. The solution is not to ”close the brackets” of “sustainable development” but to move towards “a second step” fitting more with the economic crisis and coming back to the very specificity of this concept – as it was already put forward twenty five years ago by the Brundtland report.